2014
DOI: 10.1097/mca.0000000000000106
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of patients with complex coronary artery disease according to agreement between the SYNTAX score and revascularization procedure in contemporary practice

Abstract: At our institution, there was considerable disagreement between a clinical judgment-based coronary revascularization and the SS/cSS-based allocation process as to the preferred revascularization modality for patients with complex CAD. Our results suggest that integrating the SS/cSS into the decision-making process for assigning patients to revascularization would yield better clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Specifically, the studies assessed adherence to recommendations on the performance of a revascularisation in general, 23 30 a CABG, 22 24 29 a PCI/PTCA, 22 24 25 27 an ad hoc PCI, 25 26 a PCI with prior heart team discussion 26 28 and a CA. [19][20][21] Most of the studies were based on secondary data from registries, [28][29][30] patient records [21][22][23][24][25][26] or administrative data. 22 23 27 However, two studies were based on primary data obtained from prospective records of consecutive patients (eg, severity of stenosis, symptoms, procedures).…”
Section: Methods and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, the studies assessed adherence to recommendations on the performance of a revascularisation in general, 23 30 a CABG, 22 24 29 a PCI/PTCA, 22 24 25 27 an ad hoc PCI, 25 26 a PCI with prior heart team discussion 26 28 and a CA. [19][20][21] Most of the studies were based on secondary data from registries, [28][29][30] patient records [21][22][23][24][25][26] or administrative data. 22 23 27 However, two studies were based on primary data obtained from prospective records of consecutive patients (eg, severity of stenosis, symptoms, procedures).…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Although two of the studies prospectively collected primary data, 19 20 most used secondary data that had been collected retrospectively. [21][22][23][24][25][26][27][28][29][30] Even though secondary data often represent a more easily accessible and affordable data source, they are usually not collected for the purpose of assessing guideline adherence. As a result, the database may be non-specific (ie, information is available on a more aggregate level without providing clinical details) or incomplete (ie, required information is missing entirely).…”
Section: Data Sources and Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] Even when the clinical SYNTAX score was used to predict treatment strategy, if patients with a high score disagreed to be revascularized by CABG and preferred to be treated by PCI, worse adverse outcomes were later observed.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a retrospective study has found that patients who had CABG recommended on the basis of a high SS but refused and chose PCI have an elevated risk of cardiac adverse events. [53] Even when the clinical SS is used to predict the best treatment approach, if patients with a high score refuse CABG in favor of PCI, subsequent outcomes have been found to be poorer.…”
Section: Advantages Of Cabg Vs Pcimentioning
confidence: 99%